Debriefing Methodologies in Nursing Simulation: An Exploratory Study of the Italian Settings. - Lomuscio, Sonia; Capogna, Emanuele; Sironi, Stefano; Sguanci, Marco; Morales Palomares, Sara; Cangelosi, Giovanni; Ferrara, Gaetano; Mancin, Stefano; Amodeo, Antonio; Destrebecq, Anne; Parozzi, Mauro; Dal Bello, Susy (Nursing Reports, 2025)
Background: As part of simulation-based learning, it is well known that debriefing plays a crucial role; ineffective debriefing can lead to a reiteration of errors in decision-making and a poor understanding of one's limitations, compromising the learner's psychological safety and making future simulated learning experiences less effective. In Italy, although simulation has been used in nursing education for more than 20 years, there is a general lack of data regarding the elements of debriefing. Methods: An exploratory, cross-sectional, multicenter nationwide study was conducted to identify current debriefing practices in Italian simulation-based nursing education. A non-probability sample of all directors of the Italian Bachelor school of Nursing and the directors of simulation centers on Italian national territory was surveyed with an online questionnaire. Results: Fifty-four nursing degree programs and 11 simulation centers participated in the survey. Significant differences were found between debriefing practices used by simulation centers and those used by the Bachelor School of Nursing. Specifically, differences concerned the training of debriefers, the knowledge of a debriefing framework, the use of different rooms for debriefing and the time spent on this activity. Conclusions: There is an emerging need for a harmonization process in Italian nursing education debriefing practices that would align the current reality with the best practices of the literature.